Justice in Proportional Inheritance Distribution Based on Contemporary Perspective - Dedi Pahroji; Puti Priyana; Margo Hadi Pura; Athari Farhani; Faiqah Nur Azizah (Faculty of Law, Universitas Pekalongan, 2025)
This research focuses on the application of a sense of justice in the distribution of inheritance according to contemporary Fiqh Mawaris and compares it with Islamic inheritance law and analyzes the judge's considerations in related cases. This research uses normative juridical methods with a literature approach (statute approach), comparative analysis, concept analysis and case analysis. The results of this research conclude that the sense of justice that develops in society must be taken into account when determining the distribution of inheritance. The concept of dividing inheritance property 2:1 as regulated in the Compilation of Islamic Law and referring to the arguments of the Al-Qur'an is a proportional distribution, but in certain conditions it is also not an absolute basis without considering the current conditions of society. Where currently it is not uncommon for women to take on the role of men in certain conditions, so that in terms of inheritance the division between men and women with the 1:1 concept can be considered to fulfill a sense of justice and can be said to be a proportional distribution as well